2021
DOI: 10.1038/s41598-021-00904-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence and visual prognostic factors of polypoidal choroidal vasculopathy: 5-year results

Abstract: This retrospective study aimed to evaluate the factors affecting recurrence and visual prognosis in patients with treatment-naïve subfoveal polypoidal choroidal vasculopathy (PCV). Patients who had received three consecutive intravitreal injections of ranibizumab or aflibercept and had reached remission were enrolled. They were divided into a group without recurrence (group 1, 26 eyes) and a group with recurrence (group 2, 121 eyes) and followed up for at least 5 years. Patients in group 2 received additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, no differences in characteristics were noted between the responder and non-responder groups. In addition, although previous studies have shown that imaging features-including choroidal vascular hyperpermeability, presence of polyp clusters, greater linear dimension of the lesion, largest polyp diameter, and choroidal thickness-can influence the treatment outcomes [22][23][24], there was no significant difference in these features between the responder and the non-responder group. However, we postulate that these results were partially induced by the small sample size in this study.…”
Section: Discussionmentioning
confidence: 78%
“…However, no differences in characteristics were noted between the responder and non-responder groups. In addition, although previous studies have shown that imaging features-including choroidal vascular hyperpermeability, presence of polyp clusters, greater linear dimension of the lesion, largest polyp diameter, and choroidal thickness-can influence the treatment outcomes [22][23][24], there was no significant difference in these features between the responder and the non-responder group. However, we postulate that these results were partially induced by the small sample size in this study.…”
Section: Discussionmentioning
confidence: 78%
“…Younger age at onset, higher choroidal vascularity index, and presence of CVH were related with low risk of recurrence. For those with recurrence, having large lesion, and cluster polypoidal lesions were found to be associated with worse final visual acuity 119…”
Section: Updates On Treatment Of Pcvmentioning
confidence: 91%
“…For those with recurrence, having large lesion, and cluster polypoidal lesions were found to be associated with worse final visual acuity. 119 RPE and Retina. In a retrospective series of patients with PCV treated with either ranibizumab or aflibercept in a PRN regimen and 24-month follow-up, 10.5% developed RPE atrophy.…”
Section: Specific Characteristicsmentioning
confidence: 99%
“…Polypoidal choroidal vasculopathy (PCV) is a variant of neovascular AMD, characterized by aneurysmal dilatations at the end of a type 1 neovascularization [ 3 – 5 ]. While randomized controlled trials have reported visual improvement up to 2 years [ 6 9 ], there is a paucity of long-term outcome data [ 10 , 11 ]. The EVEREST II study compared the efficacy and safety of intravitreally administered ranibizumab (IVR) alone or in combination with photodynamic therapy (PDT) over a 2-year period.…”
Section: Introductionmentioning
confidence: 99%